2021
DOI: 10.21037/atm-21-1141
|View full text |Cite
|
Sign up to set email alerts
|

Perioperative safety and feasibility outcomes of stage IIIA-N2 non-small cell lung cancer following neoadjuvant immunotherapy or neoadjuvant chemotherapy: a retrospective study

Abstract: Background: We sought to determine the perioperative safety and feasibility outcomes of stage IIIA (N2) non-small cell lung cancer (NSCLC) following neoadjuvant immunotherapy or neoadjuvant chemotherapy. Methods:The clinical details of patients who attended the Affiliated Hospital of Qingdao University between January 2019 and December 2020 were retrospectively evaluated. Eligible patients had pathologically proven stage IIIA (N2) NSCLC and were randomly prescribed neoadjuvant therapy. Those in the neoadjuvant… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
14
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(16 citation statements)
references
References 38 publications
1
14
0
1
Order By: Relevance
“…25 In addition, immune-related AEs were well monitored and managed, which is consistent with the findings on immunotherapy in a series of studies. 18,19,26 Subgroup analysis demonstrated that patients with negative PD-L1 expression did not have worse radiological or pathological responses and survival benefit. In another words, patients benefited from neoadjuvant chemoimmunotherapy regardless of PD-L1 expression, which was consistent with the findings of several studies.…”
Section: Discussionmentioning
confidence: 96%
See 2 more Smart Citations
“…25 In addition, immune-related AEs were well monitored and managed, which is consistent with the findings on immunotherapy in a series of studies. 18,19,26 Subgroup analysis demonstrated that patients with negative PD-L1 expression did not have worse radiological or pathological responses and survival benefit. In another words, patients benefited from neoadjuvant chemoimmunotherapy regardless of PD-L1 expression, which was consistent with the findings of several studies.…”
Section: Discussionmentioning
confidence: 96%
“…A meta-analysis showed that neoadjuvant chemotherapy had a significant survival benefit for patients with NSCLC, with a 5-year OS benefit increased by 5%. 6 Huang et al reported a better pathological response in neoadjuvant immunotherapy compared with neoadjuvant chemotherapy in stage III (N2) NSCLC, 18 with a MPR of 12.8% and a pCR of 2.6% in the neoadjuvant chemotherapy group. In terms of neoadjuvant chemoradiotherapy, a retrospective multi-institutional Phase II study compared the pathological responses of neoadjuvant chemotherapy or chemoradiotherapy in stage III (N2) NSCLC, 28 which reported a MPR of 54.5% in the tumor and 80% downstaging in the neoadjuvant chemoradiotherapy group, and 9.5% and 33.3% in the neoadjuvant chemotherapy group, respectively.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…A total of 4143 references were identified through the electronic search; 2914 potentially relevant articles remained for screening after the removal of duplicated studies. After applying the selection criteria, 33 studies remained for full assessment, and 18 publications from 16 studies were selected for quantitative analysis [5][6][7][8][9][10][11][12][13][14][15][16][17][18][19][20][21][22]. Two publications reported on the same trials with a focus on different clinical outcomes [6,7,12,13].…”
Section: Quantity and Quality Of Trialsmentioning
confidence: 99%
“…Pathological response outcomes were reported as 'major pathological response' (MPR) when less than 10% of the viable tumor was identified in the primary lesion, and 'complete pathological response' (pCR) when no viable tumor was identified. However, some studies specifically reported pCR when both the primary lesion as well as the sampled lymph nodes were free from any viable tumor [5][6][7]9,10,[12][13][14]17,19,22], whereas others did not specify if nodal assessments were performed for pathological responses [8,11,15,16,18,20,21]. In addition, two studies defined MPR and pCR as being mutually exclusive, whereby patients who achieved a complete pathological response were not included within the group defined as a major pathological response [9,21].…”
Section: Pathological Responsementioning
confidence: 99%